THE IMPORTANCE OF ADJECTIVES IN HUMANS’ SPEECH - Khaydarova Kamola Davranovna; Chorshanbiyeva Kimyo Chori qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The article contains analyzes of the importance of speech in human life, adherence to speech culture and the importance of quality in the speech process. In this article, the speech culture of a person, the culture of text and its correct delivery to the listener in an oral way, the use of adjectives in speech expression, the place of phrases with an adjective component in speech, and the organization of the structure of a person's language culture in general information will be provided.